Prevalence and risk factors of hemorrhoids in Jazan Region, Saudi Arabia: A cross-sectional study - Hassan Mashbari; Othman Iskander; Khalid Alyahyawi; Shahd O. AlMarei; Afnan Q. Maashi; Mashael S. Mahnashi; Maram Y. Allami; Fadiyah K. Ageeli; Asma M. Ashiri; Jawahir M. Homadi; Mawaeed A. A. Thakir; Ethar I. Abujabir (Journal of Family Medicine and Primary Care)
Background: Hemorrhoids a prevalent anorectal disorder, have gained rising attention due to their impact on public health and quality of life. Despite their significance, limited research has addressed their prevalence and associated risk factors in the Jazan Region, Saudi Arabia. Thus, this study was designed to determine the prevalence and risk factors of hemorrhoids in Jazan region, Saudi Arabia. Methods: This was a cross-sectional study conducted in the Jazan region, Saudi Arabia, from January to June 2023. Encompassing both urban and rural areas, the study focused on individuals aged 18 and above, excluding those with communication difficulties, mental illness, or severe conditions. Employing random sampling, a sample size of 420 was determined to ensure representation, and participants were selected using a systematic random sampling technique. The analysis was performed using R version 4.2.3. Results: The study included 475 participants, predominantly females (72.57%), aged 25 to 44 (53.38%), with higher education (82.28%) and Saudi nationality (98.31%). Prevalence of hemorrhoids was 13.29%, with 5.27% external, 2.53% internal, and 0.21% thrombosed hemorrhoids. Constipation (OR: 2.28, P = 0.001) and family history (OR: 4.77, P < 0.001) were significant risk factors. Complications were reported by 5.70%, including ulceration (1.05%) and severe bleeding (1.05%). Social norms hindered treatment seeking for 55.49%. While age correlated (P = 0.002 and P = 0.003) with increased odds of hemorrhoids, gender, marital status, nationality, education, employment, smoking, exercise, and fiber intake showed no significant associations. Conclusion: In conclusion, the study revealed a 13.2% prevalence of hemorrhoids mostly external underscoring the significance of factors such as constipation age group, fiber intake, and family history in increasing susceptibility.